Casa de ferreiro, espeto é de pau: Gestão de recursos hídricos em duas organizações universitárias - Freitas, Wesley Ricardo de Souza; Julio, Marcos de Oliveira [UNESP]; de Castro, Rosani [UNESP]; Jabbour, Charbel José Chiappetta [UNESP] (My University, 2012)
As water is essential for human survival and university organizations are responsible for spreading new knowledge and values through teaching, research and extension, this paper examined how two university organizations deal with a most precious resources, the Water, through its environmental management activities. To communicate the survey, this article is structured in three parts: the first is a brief reflection on environmental management in the university hospitals and the issue of water resources, then presents the methodological procedures for the conduct of research. Finally, we present the empirical evidence from case studies and discussions relevant to the research, followed by proposals on best practices in managing water resources that universities could adopt under review. It can be concluded that the possession of knowledge and cutting-edge research in several areas that universities do not provide an exemplary way to manage their water resources, ie, isolated and fragmented initiatives of Colleges ALPHA and BETA do not guarantee the environmental sustainability of campus, a As one can see that the units are not achieving academic success in the overflow of its knowledge and research for an effective internal environmental management, especially its water resources.
House of smith, spit and stick: Management of water resources in two student organizations
Keywords: Environmental management; University; Water resources management